Research on Heat Dissipation Performance of Double-sided Cooling Heat Pipe Radiator of Maglev Train - Xiong WANG; Zhiyong WU; Guomeng SONG; Nan HUANG; Hongfeng WANG (机车电传动)
In view of the current situation that the traditional heat pipe radiator structure cannot meet the heat dissipation requirements of the maglev train traction converter, a double-sided cooling heat pipe radiator was proposed suitable for high heat flux density. The research methods of numerical simulation and experimental testing were used to compare the double-sided heat pipe radiator with the same volume TM36 profile radiator and CRH2 high-speed EMUs heat pipe radiator. The results showed that under the same air volume and power, the heat dissipation efficiency of double-sided heat pipe radiators with similar volumes of TM36 profile radiators was increased by 32% while the wind resistance was reduced by 35%, the heat dissipation performance of the heat pipe radiators for CRH2 high-speed EMUs was almost the same, but the cost and space could be saved by more than 50%.